TSS Tool: Automation Tool Applied in the True Single SKU Setup Environment Preparation for Multiple Devices in Parallel - Fernandes, Carol; Araújo, Charles; Oliveira, Adriano; Corrêa, Wellington; Ipê, Luan; Andrade, Paulo (Anais do Simpósio Brasileiro de Testes de Software Sistemático e Automatizado (SAST), 2024)
There is an extensive amount of mobile product models in the market. In this scenario, research institutes are involved in a stage previous to release, in order to ensure that the software meets quality standards, with stakeholders’ requirements embedded, tested and validated. All of this in a high demand scenario. These institutes are presented with the challenge of delivering software ready for release increasingly faster than before. Replacing manual processes with automation can reduce execution time in the production chain. After analyzing our own context, we concluded that True Single SKU (TSS) mobile models were a strong candidate for process improvements. These devices’ setup was a bottleneck, since execution was done 100% manually. Our objective is to assess the benefits of using an automated TSS Tool in the environment setup preparation of multiple devices in parallel. Through observational studies, we were able to reaffirm the relevance of using software automation as a strategy to reduce development time. Besides, it works in a supporting role when dealing with high demand. We observed a gain in time of up to 52% for beginner testers and 50% for experienced testers. These results were achieved when comparing manual setup activities executed with multiple devices one by one and automated setup activities with multiple devices at the same time.We concluded that we were able to save more development time and achieve more flow in the whole production chain for TSS mobile devices.